Estimation of reliability in multicomponent stress–strength based on two parameter exponentiated Weibull Distribution. Issue 15 (3rd August 2017) - Srinivasa Rao, G.; Aslam, Muhammad; Arif, Osama H.
ABSTRACT: In this research article, we estimate the multicomponent stress–strength reliability of a system when strength and stress variates are drawn from an exponentiated Weibull distribution with different shape parameters α and β, and common shape and scale parameters γ and λ, respectively. We estimate the parameters by using maximum likelihood estimation (MLE) and hence the estimate of reliability obtained applying the MLE method of estimation when samples are drawn from stress and strength distributions. The small sample comparison of the reliability estimates is made through Monte Carlo simulation.